A Chemically Induced Experimental Colitis Model with a Simple Combination of Acetic Acid and Trinitrobenzene Sulphonic Acid - Havva Yasemin Cinpolat; Güler Buğdaycı; Neriman Şengül; Hesna Müzeyyen Astarcı (Turkish Journal of Gastroenterology, 2023)
Background: It was aimed to induce a new experimental colitis model by using acetic acid and trinitrobenzene sulphonic acid together and to investigate the severity of inflammation biochemically and histopathologically in comparison with other models. Methods: Fifty-six Wistar albino male rats were randomly divided into 4 groups as control, acetic acid, trinitrobenzene sulphonic acid, and combined groups, and the animals were sacrificed following the induction of colitis on the third day and on the seventh day. The serum amyloid A and myeloperoxidase were tested in plasma samples, and the tumor necrosis factor-alpha, interleukin 33, and ST2 were assayed in colon tissue samples with enzyme-linked immunosorbent assay in addition to histopathological examination. Results: There were statistically significant differences between the combined and the control groups both on the third day and on the seventh day in all parameters. There was no difference between the acetic acid group on the seventh day and the control groups in biochemical parameters. Conclusions: The acetic acid model forms acute colitis. The combined model is found to be more successful in forming inflammation when compared to other models. Cite this article as: Cinpolat HY, Buğdaycı G, Şengül N, Astarcı HM. A chemically induced experimental colitis model with a simple combination of acetic acid and trinitrobenzene sulphonic acid. Turk J Gastroenterol. 2023;34(3):196-202.